Homeostase glicêmica da prole de ratas obesas submetidas à operação bariátrica - Pietrobon, Carla Bruna (2017)
There has been an increase in female obesity worldwide. As a consequence of these high rates the number of women of child-bearing age who seek bariatric operations has increased considerably in recent years. However, few studies showed the effects of maternal bariatric operation in their offspring. Herein, we evaluated the effects of maternal Roux-in-Y Bypass Gastric (RYBG) in Wistar rats fed cafeteria diet (CAF) upon body features and glucose homeostasis in male adult offspring. For this, rats Wistar received CAF diet for 15 weeks for obesity induction. After this period, the rats were submitted to sham operation (CAF Sham), group CAF sham (n=14) or RYGB operation, group CAF RYGB (n=20). Five weeks after the procedure, the rats were submitted at matting period. The offspring were named as operation your mothers: CAF Sham-F1 (n=28) and CAF RYGB-F1 (n=14), and received standard diet. The weaning from offspring was performed at 30 days of life. Nasoanal length, body weight, consumption and feed efficiency were evaluated weekly throughout experiment. One week before euthanasia, the animals were submitted to the glucose tolerance test and insulin. At 120 days of life, body parameters, serum parameters and morphophysiology of the pancreas were evaluated. After RYBG, female rats displayed reduction in body weight, glucose tolerance and insulin, as well as, decreased fat deposits. Despite of these maternal benefits, the offspring of dams receiving RYBG were smaller and lighter and showed a reduction in food intake than offspring of obese dams that underwent sham surgery. Although these animals presented normal glucose tolerance and glycemia, the insulin sensitivity was higher. In addition, the insulin signaling in liver and fat tissue in these offspring was normal but in skeletal muscle was reduced. Also, the offspring of dams receiving RYBG presented reduction in insulinemia and insulin secretion, but the area and mass of β-cell was higher compared to offspring of obese dams that underwent sham surgery. Maternal RYBG in obese rats alter in male offspring the body features and lead to morphofunctional alterations in the β-cells.